2006
DOI: 10.1002/elan.200503450
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum(III) Porphyrins as Ionophores for Fluoride Selective Polymeric Membrane Electrodes

Abstract: Aluminum(III) porphyrins are examined as potential fluoride selective ionophores in polymeric membrane type ionselective electrodes. Membranes formulated with Al(III) tetraphenyl (TPP) or octaethyl (OEP) porphyrins are shown to exhibit enhanced potentiometric selectivity for fluoride over more lipophilic anions, including perchlorate and thiocyanate. However, such membrane electrodes display undesirable super-Nernstian behavior, with concomitant slow response and recovery times. By employing a sterically hinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
2
39
0
2
Order By: Relevance
“…The structure of these species prevent unwanted metalloporphyrin dimer-monomer equilibria within the membrane phase of the electrode, with such chemistry leading to non-ideal response properties. Similar studies with Al(III) picket fence porphyrin (Al[PFP]) to prevent dimer-monomer chemistry have also been reported [14]. However, it was found that Al[PFP] easily forms insoluble crystals within the membrane phase and also leaches from the membrane to the water sample; hence, in spite of excellent selectivity towards fluoride, electrodes based on Al(III)-[PFP] doped membranes are not analytically useful because of their continuous loss in slope, response range and selectivity over just a few days of operation.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…The structure of these species prevent unwanted metalloporphyrin dimer-monomer equilibria within the membrane phase of the electrode, with such chemistry leading to non-ideal response properties. Similar studies with Al(III) picket fence porphyrin (Al[PFP]) to prevent dimer-monomer chemistry have also been reported [14]. However, it was found that Al[PFP] easily forms insoluble crystals within the membrane phase and also leaches from the membrane to the water sample; hence, in spite of excellent selectivity towards fluoride, electrodes based on Al(III)-[PFP] doped membranes are not analytically useful because of their continuous loss in slope, response range and selectivity over just a few days of operation.…”
Section: Introductionsupporting
confidence: 57%
“…Similarly, thus far, relatively few useful fluoride-selective polymeric membrane electrodes have been reported [8][9][10][11][12][13][14][15]. Most suffer from practical problems such as high level of interference by lipophilic anions [11,12,15], super-nernstian response slopes, sluggish and not fully reversible response properties [8,9,10,14] and short use lifetimes of the electrodes [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ISEs are also of obvious interest because they can help translate the chemistry of new substrate binding systems into tools that can be used to recognize selectively various targeted species in the presence of potentially interfering analytes. In the specific case of anion recognition, this approach has been explored extensively by Umezawa, Meyerhoff, Simon, Reinhoudt, Schmidtchen and others using a range of receptors including bis-guanidinium [1][2], porphyrins [3], protonated polyamines [4][5][6][7], and protonated sapphyrins [8][9][10], as well as a variety of Lewis acidic systems such as calixarenes [11][12][13][14][15], uranylsalenophenes [16][17], metalloporphyrins [18][19][20][21][22], metallocenes [23], other organometallic derivatives [24][25][26], and fluorinated compounds [27].…”
Section: Introductionmentioning
confidence: 99%